Síndrome de guillain-barré pós cirurgia bariátrica: relato de caso e revisão de literatura - Rodrigues, Helder Barbosa (Universidade Federal Rural do Semi-Árido, 2020)
Guillain-Barré Syndrome is an inflammatory polyneuroradiculopathy, being the most prevalent cause of acute flaccid paralysis, with an annual incidence of 1 to 2 cases per 100,000 people per year. It is clinically characterized, in its most common form, as a flaccid, symmetrical and cooled muscle paralysis of an ascending character, which may be accompanied by dysautonomies. Guillain-Barré syndrome does not have a completely clear etiopathogenesis, and is commonly attributed to an autoimmune response induced by a previous infection. The diagnosis is clinical, however, using liquid analysis and a study of nerve conduction to check and differentiate its variants. Relates the case of a 49-year-old male patient who had undergone bariatric surgery 20 days before, or who developed cold tetraparesis, of an ascending character, with protein-cytological dissociation in the liquid or Guillain-Barré axial sensory-motor variant on electroneuromyography. The patient evolved with quadriplegia and severe severe impairment requiring mechanical ventilation, even after treatment with 2 immunoglobulin cycles. The present work deals with a literature review of Guillain- Barré syndrome based on research in preferably current articles, indexed to the databases of PubMed, MEDLINE, SciELO and BVS.
Keywords: Síndrome de Guillain-Barré; Polineurorradiculopatia; Cirurgia bariátrica; CIENCIAS DA SAUDE::MEDICINA